Implementation of A School Based on A Wetland Environment From An Ecological Citizenship Perspective : Ecologycal Citizenship - Ruchliyadi, Dian Agus; Nugroho, Dedy Ari; Maulana, Muhammad Fajar; Ridha, M Kamil (Universitas Nusantara PGRI Kediri, 2023)
Humans and the environment are two things that are interconnected and cannot be separated from each other. Educating people who are aware of the importance of the environment certainly requires effort. One of them is through educational institutions. This study uses a qualitative approach by presenting data from research results. Processed and presented qualitatively. This study used observation data collection techniques, interviews and documentation. Analysis of the research data used interactive model analysis techniques (interactive model of analysis) from Miles and Huberman. In this interactive analysis model, the researcher moves on three components, namely data reduction, data display and verification. The results of this research found that the Adiwiyata Middle School curriculum always prioritizes the active involvement of all school members in environmental conservation. The organization at the Adiwiyata school in Banjarmasin City has one of its missions, namely environmental preservation. The existence of an environmentally based curriculum will create a new culture, namely an environmental culture where school residents will be more aware of the importance of protecting the environment.